Ethical entrepreneurial leadership and organizational trust for organizational sustainability - I Wayan Gde Sarmawa; Anak Agung Dwi Widyani; Ida Ayu Putu Widani Sugianingrat; Ida Ayu Oka Martini (Cogent Business & Management, 2020)
This study aims to examine and analyze the role of ethics in entrepreneurial leadership, and its influence on organizational trust and organizational sustainability. This study also analyzes the role of organizational trust in mediating the relationship of ethical entrepreneurial leadership to organizational sustainability. This research was conducted at the Village Credit Institution (Lembaga Perkreditan Desa/LPD) in Bali. The total population of active LPD in Bali in 2018 was 1,422 units. The number of samples is determined based on the Slovin formula with a precision level of 10%. The calculation results obtained a total sample of 93 LPD. The determination of the number of samples in each group is done by stratified proportional random sampling. Data collection was carried out by distributing questionnaires to the leaders of the LPD. The data collected was analyzed with the SmartPLS 3.0 program. The results of the analysis show that ethics is significantly a part of entrepreneurial leadership, so leaders who reflect entrepreneurial leadership styles and prioritize ethical behavior can be referred to as ethical entrepreneurial leadership styles. The ethical entrepreneurial leadership style shows a significant positive effect on organizational trust, but not significantly on organizational sustainability. Organizational trust has a significant positive effect on organizational sustainability. The results also show that organizational trust acts as a full mediator in the relationship between ethical entrepreneurial leadership and organizational sustainability.
Keywords: 650; ethical leadership; entrepreneurial leadership; ethical entrepreneurial leadership; organizational trust; organizational sustainability